2016
DOI: 10.1088/1742-6596/680/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Study of humidity on the structure and optical properties of cesium iodide thin film

Abstract: We report the influence of 70% 5% humid exposed air at room temperature on the structure of 500nm thick CsI film. By means of scanning electron microscopy (SEM) and X- ray diffusion (XRD) analysis, the surface morphology and polycrystalline structure were investigated. After 24 hour exposure to humid air, the grain size of CsI film has a drastic change, and so as to the preferential growth orientation. Infrared spectra showed a hydroxyl absorption peak after 3h exposure. And in long term exposure (24h), the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Figure 3b, the the additional absorption at 1721 cm −1 was the characterized absorption ester carbonyl vibration [47,48] . The peaks at 1450 cm −1 were belonged to the stretching frequency of C−H groups and the skeleton vibration from imidazole ring [49] . Through infrared analysis, it is concluded that the ionic liquid was successfully bonded to DK110.…”
Section: Resultsmentioning
confidence: 93%
“…In Figure 3b, the the additional absorption at 1721 cm −1 was the characterized absorption ester carbonyl vibration [47,48] . The peaks at 1450 cm −1 were belonged to the stretching frequency of C−H groups and the skeleton vibration from imidazole ring [49] . Through infrared analysis, it is concluded that the ionic liquid was successfully bonded to DK110.…”
Section: Resultsmentioning
confidence: 93%
“…Most notably, oxygen was present even though the precursors are oxygen-free. CsI is known to be hygroscopic. Although we stored the films in either dry or inert conditions, they were still exposed to ambient air during transfer and sample preparation. CsHCO 3 reflections appeared in the XRD pattern of the film stored in ambient air for more than a month (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Our result is consistent with the experimental results. For 500 nm thick CsI crystal, when it is under long term exposure (24 h), the absorption peak broadens with the band center shifting toward lower wave numbers [ 19 ]. The calculated reflection coefficients are shown in Figure 13 .…”
Section: Discussionmentioning
confidence: 99%